Economic burden of pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) in Finland - Pentikäinen, Markku; Simonen, Piia; Leskelä, Pauliina; Harju, Terttu; Jääskeläinen, Pertti; Wennerström, Christina; Bødker, Nikolaj; Heikkilä, Eija; Lahelma, Mari; Leskelä, Riikka-Leena; Puhakka, Airi; Heliövaara, Elina; et al. (Elsevier BV, 2025)
Objectives
Given that pulmonary arterial hypertension (PAH) and chronic thromboembolic hypertension (CTEPH) are rare yet severe subtypes of pulmonary hypertension significantly impacting patients’ lives, this study analyzed the total societal costs of these conditions in Finland.
Methods
PAH (n = 247) and CTEPH (n = 177) patients diagnosed between 2008 and 2019 were analyzed for primary and specialty outpatient visits, emergency visits, hospitalizations, home and institutional care, sick leaves, disability pensions, and drug costs for 5 years before and after diagnosis.
Results
In PAH and CTEPH, annual specialty care number of outpatient visits increased from 3.8 and 3.3 (5 years before diagnosis) to 13.8 and 9.5 one-year post-diagnosis, then decreased to 9.2 and 4.0 at 5 years post-diagnosis. Annual inpatient days rose from 2.8 and 2.7 to 16.1 and 19.7 pre-diagnosis, then fell to 10.2 and 3.5 post-diagnosis, respectively. Within 5 years post-diagnosis, in working-age 70 % PAH and 42 % CTEPH patients received disability pensions. Drug therapy accounted for most costs (67 % in PAH and 60 % in CTEPH), followed by inpatient care, disability pensions, and outpatient care. Total costs were significantly lower for CTEPH, especially after pulmonary endarterectomy. Among PAH subtypes, the highest costs were in patients with PAH associated with connective tissue diseases.
​​​​​​​
Conclusions
PAH and CTEPH cause a significant economic burden on patients and society with considerable differences depending on the PAH subtype and whether the patient has undergone PEA operation or not.